2007
DOI: 10.1159/000111766
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Abnormalities and Yq Microdeletions in Infertile Italian Couples Referred for Assisted Reproductive Technique

Abstract: This study analyses the prevalence of karyotype aberrations and Yq microdeletions in infertile couples undergoing intracytoplasmic sperm injection (ICSI). Before undergoing ICSI, each partner of 470 infertile couples was screened for karyotype aberrations by QFQ-banding technique on peripheral blood lymphocytes; male partners were also screened for Yq microdeletions. In 2.55% of the couples karyotype aberrations were found including numerical and structural alterations of autosomes and sex chromosomes. The fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…In total, data from 10,726 men and 8390 women have been evaluated, yielding mean rates of abnormal karyotypes of 3.6% and 4.2%, respectively. In contrast, the frequency of aberrations in some recently published studies varies from 2.2%-5.2% for male and 0.9%-2.34% for female patients (Kayed et al 2006;Marchina et al 2007;Riccaboni et al 2008). In the present investigation, we found the same incidence of chromosomal abnormalities (3.3%, 14/430) for both sexes.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In total, data from 10,726 men and 8390 women have been evaluated, yielding mean rates of abnormal karyotypes of 3.6% and 4.2%, respectively. In contrast, the frequency of aberrations in some recently published studies varies from 2.2%-5.2% for male and 0.9%-2.34% for female patients (Kayed et al 2006;Marchina et al 2007;Riccaboni et al 2008). In the present investigation, we found the same incidence of chromosomal abnormalities (3.3%, 14/430) for both sexes.…”
Section: Discussionmentioning
confidence: 80%
“…In the review by Mau-Holzmann (2005), only four comparable complex rearrangements have been reported: t(1;9;21), t(4;11;18), t(4;13;9) and t(8;13;16). In addition, Basaran et al (2004) detected a male with t(5;6;14) and Marchina et al (2007) a case with t(1;2;8). As stated by Chantot-Bastaraud et al (2008), the probability of finding chromosomally balanced spermatozoa for ICSI is very low in these cases.…”
Section: Chromosome Anomalies In Icsi Patientsmentioning
confidence: 98%
“…Several studies have shown a higher prevalence, in comparison to the general population, of chromosomal abnormalities in both men and women with fertility problems [1][2][3][4][5][6][7][8][9][10]. Carriers of chromosomal anomalies are at increased risk to produce genetically unbalanced gametes and consequently, in addition to reproductive impairment, to have an increased risk of adverse pregnancy outcomes such as miscarriage, still birth, and malformed offspring [11].…”
Section: Introductionmentioning
confidence: 99%
“…5 Spermatozoa selection for ICSI is typically based on motility and morphology attributes, without information about the chromosomal status. 6 In children born after standard in vitro fertilization (IVF) and ICSI, the rate of major congenital malformations is around 4%.…”
Section: Introductionmentioning
confidence: 99%